Evaluation of polyunsaturated fatty acids content in the three stages of breast milk: colostrum, transitional and mature milk of a nursing mother submitted to Roux-en-Y gastric bypass surgery two months prior to pregnancy: Case study (Research, Society and Development, 2023)
The purpose of this case study was to investigate polyunsaturated fatty acids in colostrum, transitional milk and mature milk of a nursing mother attended to Roux-en-Y gastric bypass two months prior to pregnancy.  For this, was collected 2ml (colostrum), 4ml (transitional milk) and 4ml (mature milk) samples obtained by manual expression of the breast that was not sucked in the last feeding, in the morning and placed in Eppendorfs-type microtubes. The fatty acid composition was performed by means of gas chromatography. The mean proportions of fat in colostrum, transition milk and mature milk were: eicosapentaenoic acid: 0.06%; 0.05% and 0.06%; docosahexaenoic acid: 0.12%, 0.08% and 0.09%; arachidonic acid: 0.58%, 0.37% and 0.42%, respectively; trans fatty from the industrial process: 0.11%, 0.08% and 0.12% and trans fatty from ruminant sources (0.09%, 0.10% and 0.12%, respectively. The relevance of this case study lies in the fact that it shares knowledge about on the fatty acid composition of breast milk from a nursing mother post Roux-en-Y gastric bypass. The mean linoleic acid and alpha-linolenic acid found in the mature milk was below the means found in studies carried out in Brazil from eutrophic women who did not underwent bariatric surgery. In this study, trans fatty acids were found in maternal milk but considered low values. As a relevant recommendation for future work, it is suggested that research be carried out with a larger population undergoing such a procedure to investigate the composition of polyunsaturated fatty acids in breast milk.